Mempersiapkan Generasi Emas 2045: Pentingnya Literasi Digital Sejak SD - Aulia Yurniati; Natasya Yulindra Putri; Salwa Sausan; Ari Suriani (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
Indonesia's Golden Vision 2045 demands the readiness of superior, creative, and adaptive human resources in the face of rapid digital technological advancements. Digital literacy is one of the primary foundations that must be instilled from an early age, particularly at the elementary school level. This article aims to comprehensively examine the importance of digital literacy at the elementary school level, its role in shaping 21st-century character and skills, and the challenges and strategies for its implementation in elementary education. Through a literature review method, this article analyzes various research findings and best practices related to strengthening digital literacy in elementary school-aged children.The results show that digital literacy not only enhances students' technical skills in operating digital devices but also fosters critical thinking, creativity, collaboration, and effective communication. Additionally, digital literacy plays a crucial role in building digital ethics awareness and cybersecurity, as well as promoting reading interest through interactive learning media. However, challenges persist, including limited facilities, uneven teacher competence, and a lack of integration of digital literacy in the curriculum. To overcome these obstacles, synergy is needed between schools, governments, and communities in providing infrastructure, teacher training, and developing relevant curricula.Thus, strengthening digital literacy from elementary school is a strategic step in preparing a smart, critical, and competitive generation, while supporting the achievement of Sustainable Development Goals (SDGs) and Indonesia's Golden Vision 2045.